Analisis Persepsi Kepuasan Kerja Perawat Pada Ruang Rawat Inap RSUD: Analisis Persepsi Kepuasan Perawat - Hajirah Hajirah (Yayasan Ekselensi Daya Indonesia, 2025)
This study aims to determine the influence of incentives and work environment directly and indirectly on job satisfaction through nurses' self-efficacy. The type of research used is a survey method with data collection through observation methods and distributing questionnaires. This study was conducted at the Regional General Hospital involving 80 nurses in the inpatient room. The data that has been collected is then explained using Structural Equation Modeling analysis with the Covariance approach, namely SEM PLS. The results of this study prove that (1) incentives have a positive and significant effect on nurses' job satisfaction both directly and indirectly through nurses' self-efficacy in the inpatient room of the Regional General Hospital, and (2) the work environment has a positive and significant effect on nurses' job satisfaction both directly and indirectly through nurses' self-efficacy in the inpatient room of the Regional General Hospital. Therefore, the hospital needs to pay attention to providing incentives and a conducive work environment to improve nurses' self-efficacy and job satisfaction to find out incentives and work environment directly and indirectly on job satisfaction through nurses' self-efficacy.